Wireworms in Florida Sugarcane - R. H. Cherry; M. Karounos (EDIS, 2021)
Wireworms, the larval stage of a click beetle, often cause severe damage to numerous crops in Florida. At least twelve species of wireworms have been found in southern Florida, but only the corn wireworm, Melanotus communis, is considered to cause significant economic damage to sugarcane. Since M. communis is the important wireworm species, the rest of this document will pertain to this species. Generally, wireworms are a pest of newly planted sugarcane and only rarely a pest in ratoon sugarcane. More studies are needed, but the current information suggests substantial percentages (e.g. 40% or more) of wireworms could be killed by flooding but, in general, the flood duration had to be at least 4 to 5 weeks at water temperatures above 24 °C. Soil insecticides are generally used in newly planted sugarcane for wireworm control. Insecticides are not used for wireworm control in ratoon sugarcane. Pheromone traps are untested in Florida sugarcane for click beetles but have an important function in for both mass trapping and monitoring in other agricultural systems.